2014
DOI: 10.1007/s10900-014-9894-y
|View full text |Cite
|
Sign up to set email alerts
|

Living Environment Matters: Relationships Between Neighborhood Characteristics and Health of the Residents in a Dutch Municipality

Abstract: Characteristics of an individual alone cannot exhaustively explain all the causes of poor health, and neighborhood of residence have been suggested to be one of the factors that contribute to health. However, knowledge about aspects of the neighborhood that are most important to health is limited. The main objective of this study was to explore associations between certain features of neighborhood environment and self-rated health and depressive symptoms in Maastricht (The Netherlands). A large amount of routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
4
57
0
1
Order By: Relevance
“…One medium-quality found no significant positive association between mental health and the objectively assessed quality of the green areas, but did find a significant positive association between mental health and the quality of streetscape greenery (van Dillen et al, 2011). The other two studies reported that higher satisfaction with green space in the residence area was significantly associated with lower odds of psychological distress (Putrik et al, 2014) or higher odds of not being in the lowest quartile of mental health (Guite et al, 2006).…”
Section: Associations With Quality Of Green Spacementioning
confidence: 90%
See 3 more Smart Citations
“…One medium-quality found no significant positive association between mental health and the objectively assessed quality of the green areas, but did find a significant positive association between mental health and the quality of streetscape greenery (van Dillen et al, 2011). The other two studies reported that higher satisfaction with green space in the residence area was significantly associated with lower odds of psychological distress (Putrik et al, 2014) or higher odds of not being in the lowest quartile of mental health (Guite et al, 2006).…”
Section: Associations With Quality Of Green Spacementioning
confidence: 90%
“…The findings of three medium-quality studies consistently showed a positive association between quality of green space and perceived general health (Table 1) (Agyemang et al, 2007;Putrik et al, 2014;van Dillen et al, 2011). Two studies showed that the group of people that was more dissatisfied with the quality of the green spaces in their neighbourhood had respectively 64% (Agyemang et al, 2007) and 6 percent % (Putrik et al, 2014) higher odds of reporting poor perceived general health, compared to the group that was less dissatisfied.…”
Section: Associations With Quality Of Green Spacementioning
confidence: 95%
See 2 more Smart Citations
“…2,[4][5][6][7]9 Similarly epidemiological studies have shown that noise exposure is associated with self-reported health, 56 depression, 56,57 cardiovascular disease, [58][59][60][61][62] and mortality. 62,63 These associations often persist after adjustment for classic behavioral and biomedical risk factors, suggesting that other factors may partly explain these associations.…”
Section: Discussionmentioning
confidence: 99%